1983
DOI: 10.1063/1.94420
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic electronic defects at the Si-SiO2 interface

Abstract: On unannealed, thermally oxidized silicon, electron spin resonance reveals an oriented interface defect which is termed the Pb center and identified as the trivalent silicon defect. Deep level transient spectroscopy (DLTS) reveals two broad characteristic peaks in the interface-state distribution: one ∼0.3 eV above the silicon valence-band maximum and a second ∼0.25 eV below the conduction band. Isochronal anneals of oxidized silicon, coated with aluminum, show that the spin density and the densities of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(40 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…At 300°C, all interface states have recovered after 20h, while at 150°C, only 3.5% have been repassivated by hydrogen species. These results are in agreement with results concerning the diffusion of hydrogen species [10]- [11].…”
Section: B Temperature Effect On Relaxationsupporting
confidence: 94%
“…At 300°C, all interface states have recovered after 20h, while at 150°C, only 3.5% have been repassivated by hydrogen species. These results are in agreement with results concerning the diffusion of hydrogen species [10]- [11].…”
Section: B Temperature Effect On Relaxationsupporting
confidence: 94%
“…[210][211][212] It could also be shown that these P b centers are indeed the main source for the interface trap states. [213][214][215][216][217][218][219] Furthermore, it was found that the P b centers correspond to trivalent Si atoms bonded to just three other Si atoms. 214,220 In a crude approximation, one could say that the interface trap states are nothing more than Si dangling bonds; and thinking of interface states as dangling Si bonds, it is also intuitively understandable that they can act as both donors and acceptors.…”
Section: Surface States and Charge Carriersmentioning
confidence: 99%
“…The large peak corresponds to the deep level at 0.3 eV above the silicon valence band maximum (E v C 0.3 eV). 7 This coincides with the reported interface gap state between the silicon substrate and the oxide layer, which is called the Pb centre. Figure 5 shows the correlation between the average intensity of the band-edge emission and the interface gapstate density.…”
Section: Resultsmentioning
confidence: 53%